Strategi Pengembangan Digitalisasi UMKM Di Kecamatan Amarasi Kabupaten Kupang - Siahaan, Moni; Samadara, Selfesina; Bire, Amran Rohi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
The industrial revolution requires individuals to think critically and creatively, implemented through entrepreneurship in the form of micro, small, and medium enterprises (MSMEs), which have become one of the promising business potentials and opportunities. MSMEs are the largest economic actors in the Indonesian economy and play a significant role in building and growing the economy, especially in Indonesia. In facing competition, many business actors use various strategies to develop their trading businesses. One creative strategy to face competition is the strategy of digitalization development. This research aims to identify and analyze the digitalization development strategies and the priority strategies that can be used by MSMEs located in Amarasi District. The research method used is descriptive analysis. The population in this study consists of 24 MSMEs with various characteristics. The sample for this research uses purposive sampling by establishing criteria, resulting in 8 MSMEs. The analysis technique used is SWOT analysis. The outcomes of this research are: 1) Digitalization Development Strategies for MSMEs in Amarasi District, Kupang Regency 2) Publication in a National Accredited Journal Sinta. Keywords: Strategy, business, development, digitalization, MSMEs